2020
DOI: 10.1093/geronb/gbaa080
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Effects on Longitudinal Semantic Processing, Working Memory, and Cognitive Speed

Abstract: Abstract OBJECTIVES To better understand and compare effects of aging and education across domains of language and cognition, we investigated whether 1) these domains show different associations with age and education, 2) these domains show similar patterns of age-related change over time, and 3) education moderates the rate of decline in these domains. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
3
8
0
Order By: Relevance
“…The discrepant findings among these studies are likely due to their differences in the length of the follow-up interval. The follow-up interval between the two timepoints in Vonk et al’s (2020) research was 4∼8 years, whereas in the other two research (i.e., Charlton et al, 2010 ; Lövdén et al, 2014 ), the age interval was about 2 years which is similar to the current study. Therefore, future studies with a longer follow-up interval or more times of follow-up are warranted.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The discrepant findings among these studies are likely due to their differences in the length of the follow-up interval. The follow-up interval between the two timepoints in Vonk et al’s (2020) research was 4∼8 years, whereas in the other two research (i.e., Charlton et al, 2010 ; Lövdén et al, 2014 ), the age interval was about 2 years which is similar to the current study. Therefore, future studies with a longer follow-up interval or more times of follow-up are warranted.…”
Section: Discussionsupporting
confidence: 84%
“…First, in the current study, only a period of 1–2 years follow-up interval was performed, it is likely that the period is too short to be sensitive enough to reveal the aging process. For example, in the literature, Charlton et al (2010) and Lövdén et al (2014) using a follow-up approach likewise did not find an aging effect on cognitive changes, but Vonk et al (2020) found a linear aging effect in working memory and cognitive speed. The discrepant findings among these studies are likely due to their differences in the length of the follow-up interval.…”
Section: Discussionmentioning
confidence: 95%
“…Differences in the magnitude of effect sizes across picture naming, semantic fluency, vocabulary, and WAIS Information may be caused for various reasons. Semantic cognition has multiple components, including semantic control, semantic memory efficiency, and semantic representation ( Jefferies, 2013 ; Vonk et al, 2020 ; Whitney et al, 2011 ). Different semantic tasks may tap into these components with different weights, which may make the tasks differentially sensitive to early cognitive symptoms in the course of Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large body of research has demonstrated the role of subtle semantic decline in early stages of the disease or in individuals at high risk for Alzheimer’s disease (e.g., Chertkow et al, 2008 ; Papp et al, 2016 ; Vonk et al, 2019a ). While a decline in episodic memory is not only present in Alzheimer’s disease but to a lesser extent also in normal aging, several aspects of semantic cognition stay relatively intact with normal aging ( Horn and Cattell, 1966 , 1967 ; Park et al, 2002 ; Salthouse, 2010 ; Vonk et al, 2020 ). Therefore, semantic cognition could play an important diagnostic and prognostic role in preclinical Alzheimer’s disease ( Venneri et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of aging on physiological cognition are extensively studied, 56–58 the assessment of cognitive aging in midlife using simple tests suitable for use in a clinical setting, remains poorly investigated 59–62 . We here show that cognitive functions all undergo measurable, significant, and progressive deterioration during midlife aging with psychomotor speed most vulnerable to the effects of aging.…”
Section: Narrativementioning
confidence: 77%